Implementation of East Javanese Local Culture in Graphic Design Elements in Students’ Final Projects: A Literature Review - Patria, Asidigisianti Surya; Hafidz, Abdul; Nurwicaksono, Bayu Dwi; Wardani, Ayusta Lukita; Laksmi, Arieviana Ayu; Kurniawan, Yudiyanto Tri; Hidayanti, Henny; Machfud, Mochammad Abdul; Fatahillah, Rizal Sofyana; Kasdan, Junaini Binti; Tangkin, Hong; Apriyansyah, Bahalwan; Pratama, Hanny Chandra; Nugroho, David (Universitas Ahmad Dahlan, 2025)
The background of this research departs from the challenges of globalization that cause visual homogenization and erode local cultural identity. Graphic design is a strategic medium in bridging tradition with modernity, by adapting cultural elements such as batik motifs, Javanese script typography, to cultural icons Reog and Karapan Sapi. This study aims to analyze the integration of East Java local wisdom values in contemporary graphic design through a literature study approach and descriptive qualitative analysis. The research method was carried out by reviewing 215 articles selected using the PRISMA protocol until there were 15 relevant main sources. The results of the study show that there are four main trends in graphic design based on local wisdom, namely the symbolization of performance culture and language (30%), culinary branding and local products (29%), the revitalization of cultural narratives on digital platforms (22%), and the abstraction of traditional crafts into visual assets (18%). The value of the interconnectedness between keywords shows that graphic design is now strongly integrated with interactive technology, education, and the creative economy. In conclusion, the application of East Java's local wisdom in graphic design not only strengthens the region's visual identity but also opens up opportunities for sustainable creative economy innovation.